A novel insight in the diagnosis of peripheral primitive neuroectodermal tumors: a retrospective analysis of 23 patients - Li, Tao; Li, Hongsheng; Zhao, Haitao; Zhou, Wenlan; Wang, Quanshi; Hu, Kongzhen; Huang, Shun; Wu, Hubing; Fu, Lilan (Translational Cancer Research, 2018)
Background: Peripheral primitive neuroectodermal tumors (pPNETs) are rare, small, round cell tumors with high malignancy and invasiveness and a poor prognosis. 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) is important in the diagnosis of pPNETs, but the current literature on PET/CT imaging of pPNETs is limited to case reports with low-quality evidence. Methods: This study retrospectively analyzed the 18F-FDG PET/CT images of 23 patients with pPNETs. Clinical information and 18F-FDG PET/CT data were collected to analyze the PET/CT features of primary and metastatic lesions and to explore the pathological morphology, metabolism, and distribution patterns of pPNETs. Results: Of the 23 pPNET patients, 18 were male, with an average age of 26.22 years (range, 12 to 41 years). The location of the primary lesion was bone in 16 patients and non-skeletal (muscle, lung, liver, kidney, testis and mediastinum) in 7. 18F-FDG PET/CT of all patients showed a soft tissue mass with a significantly intense 18F-FDG uptake. The maximum diameter of the lesion was 7.64±2.38 cm, and the maximum standard uptake value (SUVmax) was 11.27±3.80. Primary pPNETs with ill-defined borders, heterogeneous density and invasion into the adjacent tissues were observed in 73.9% (17/23) of the patients. Necrosis or cystic changes were found in 52.17% of the lesions. No calcification was noted in any lesions. Metastases were observed in 43.5% (10/23) of the patients, including hematogenous metastases to the bone (7 patients), bilateral lungs (4 patients), liver (3 patients), vascular tumor thrombus (2 patients), and metastasis to the pericardium (1 patient); 13.0% (3/23) of patients had lymph node metastases. The rate of multiple metastases was higher in patients with primary non-skeletal pPNET than in those with primary bone pPNET [6/7 (85.7%) vs. 4/16 (25%)]. Conclusions: Both primary and metastatic pPNETs lesions showed high uptake of 18F-FDG on 18F-FDG PET/CT imaging, which has high detection sensitivity. 18F-FDG PET/CT is of great value for the diagnosis, differential diagnosis, clinical decision-making, evaluation of efficacy, and recurrence assessment of pPNETs.